An EAP Theme and Task-Based Approach within a University Context - Olga Lucia Grajales; Maria Consuelo Martínez de Gutiérrez; Adriana Valencia Pérez (Asociación Colombiana de Profesores de Ingles, 2016)
This paper discusses an approach that integrates theme and task-based instruction in English for Academic Purposes. It is argued that if students are actively engaged in meaningful related theme-based tasks, they will be exposed to real language which will help them develop their communicative competence. Likewise, students' awareness of reality as well as of their critical thinking skills can be strengthened while applying different language strategies in a particular task. Moreover, global issues can be approached from different perspective allowing interdisciplinary work. The approach here described is based on an analysis of the learners' needs, which permits knowledge of the cognitive and emotional dimensions of the student so that the learning goals can be specified. Finally, on-line support through e-learning within classroom instruction enhances autonomous language learning.